Autochthonous Case of Eosinophilic Meningitis Caused by Angiostrongylus cantonensis, France, 2016 - Nguyen, Yann (Emerg Infect Dis, 2017)
We report a case of a 54-year-old Moroccan woman living in France diagnosed with eosinophilic meningitis caused by Angiostrongylus cantonensis. Diagnosis was based on clinical symptoms and confirmed by testing of serum and cerebrospinal fluid samples. Physicians should consider the risk for A. cantonensis infection outside of endemic areas.